(untitled) (Kinesiology, 2017)
The aim of this study was to investigate the intermediate learners’ choice of self-as-a-model strategies for learning the front crawl swim by extending the amount of practice. Participants (n=40) were divided into three groups: choice (free to choose to watch a video footage of their best or overall performance anytime during a practice), yoked (paired to the learners of the choice group), and control group (did not watch any video). Experimental design also involved a pretest, eigh tacquisition blocks, and a 48-hour retention test. The measures included a qualitative analysis of the front crawl swim and the rate of self-efficacy belief questionnaire. Results showed better learning of the front crawl swim for the choice group in comparison to the yoked and control group. It was also verified that the belief of self-efficacy improved in the choice and yoked groups. Most learners chose self-observation of their overall performance during the entire practice. The rest of learners waved in their choices. Self-observation of either the best or overall performance had similar effects on learning the front crawl swim. In conclusion, to provide learners with freedom of choice during the extended acquisition phase was positive for motor learning, regardless of whether or not there were changes in their choices. Key words: freedom of choice, self-observation strategies, motor learning, amount of practice